Expression of ADAMTS13 in Normal and Abnormal Placentae and Its Potential Role in Angiogenesis and Placenta Development. Issue 9 (September 2017) - Xiao, Juan; Feng, Yun; Li, Xueyin; Li, Wei; Fan, Lei; Liu, Jing; Zeng, Xue; Chen, Kaiyue; Chen, Xi; Zhou, Xiaoshui; Zheng, X. Long; Chen, Suhua
Abstract : Objective—: ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type 1 repeats, member 13) is primarily synthesized in liver. The biosynthesis of ADAMTS13 and its physiological role in placenta are not known. Approach and Results—: We used real-time polymerase chain reaction, immunohistochemistry, and Western blotting analyses, as well as proteolytic cleavage of FRETS (fluorescent resonance energy transfers)-VWF73, to determine ADAMTS13 expression in placenta and trophoblasts obtained from individuals with normal pregnancy and patients with severe preeclampsia. We also determined the role of ADAMTS13 in extravillous trophoblasts using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, wound scratch assay, transwell migration assay, tube formation assay, and tissue outgrowth assays. We showed that full-length and proteolytically active ADAMTS13 was expressed in normal human placenta, primarily in the trophoblasts and villous core fetal vessel endothelium during pregnancy. Placental expression of ADAMTS13 mRNA, protein, and proteolytic activity was at the highest levels during the first trimester and significantly reduced at the term of gestation. Additionally, significantly reduced levels of placental ADAMTS13 expression was detected under hypoxic conditions and in patients with preeclampsia. In addition, recombinant ADAMTS13 protease stimulated proliferation, migration, invasion, and network formation of trophoblastic cells in culture. Finally, knockdown of ADAMTS13 expression attenuated the ability of tube formation in trophoblast (HTR-8/SVNEO) cells and the extravillous trophoblast outgrowth in placental explants. Conclusions—: Our results demonstrate for the first time the expression of ADAMTS13 mRNA and protein in normal and abnormal placental tissues and its role in promoting angiogenesis and trophoblastic cell development. The findings support the potential role of the ADAMTS13–von Willebrand factor pathway in normal pregnancy and pathogenesis of preeclampsia. Abstract : Supplemental Digital Content is available in the text.